El alga Digenea simplex (Ceramiales: Rhodomelaceae) en México: variación biogeográfica - Dreckmann, Kurt M (Universidad de Costa Rica, 1994)
The alga Digenea simplex (Wulfen) C. Agardh has been reported in forty seven Mexican localities. A detailed description of reproductive and morphological features is given hete for the first time. Its presence in Bahía Banderas, Nayarit (Pacific of Mexico) is a first record. The lack of sexual structures suggests that Mexican populations are monophasic. The only morphological difference observed in distant populations (Nayarit, Tamaulipas and Quintana Roo) is the size of individual plants (not statistically significant). There ís not enought evidence to support taxonomic seggregates.